2018
DOI: 10.1029/2018jc014342
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Internal Wave‐Driven Mixing and Stratification in Canadian Arctic Shelf and Shelf‐Slope Waters

Abstract: Our understanding of ocean mixing is challenged by its patchy, episodic nature and a scarcity of direct measurements, especially in the Arctic Ocean. In this study, we exploit a historical record of nearly 3,000 conductivity‐temperature‐depth profiles collected in the shelf and shelf‐slope waters of the Canadian Arctic Ocean from 2002 to 2016 to characterize the variability of 28,872 internal wave‐driven turbulent dissipation and mixing rate estimates from a finescale parameterization. We find that these estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 56 publications
7
40
0
Order By: Relevance
“…The overall mean size of frazil ice particles in freshwater of 0.52 mm was slightly larger than in saline water. This value falls within the reported ranges of previous studies of 23 µm to 5 mm (Gosink and Osterkamp, 1983;Daly and Colbeck, 1986;Ye et al, 2004;Clark and Doering, 2006;Mc-Farlane et al, 2015. The average overall mean particle size in saline water was 0.46 mm.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overall mean size of frazil ice particles in freshwater of 0.52 mm was slightly larger than in saline water. This value falls within the reported ranges of previous studies of 23 µm to 5 mm (Gosink and Osterkamp, 1983;Daly and Colbeck, 1986;Ye et al, 2004;Clark and Doering, 2006;Mc-Farlane et al, 2015. The average overall mean particle size in saline water was 0.46 mm.…”
Section: Discussionsupporting
confidence: 91%
“…In a similar series of experiments in the same tank, McFarlane et al (2015) found that the tank-averaged turbulent kinetic energy dissipation rate was ∼ 3.4 × 10 −2 m 2 s −3 at a propeller speed of 325 rpm, and this fell within the range of dissipation rates estimated for rivers in Alberta. Dissipation rates in the ocean range from ∼ 10 −2 to 10 −9 m 2 s −3 (Banner and Morrison, 2018;Wang and Liao, 2016), with a reported lower range in the polar regions ranging from ∼ 10 −3 to 10 −10 m 2 s −3 (Chanona et al, 2018;Scheifele et al, 2018). Therefore, the dissipation rate generated in these experiments falls within the upper limits of values observed in the ocean.…”
Section: Experimental Set-up and Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…While less sea ice may enhance the input of wind energy into the ocean (Rainville and Woodgate, 2009;Dosser and Rainville, 2016), this energy may be dissipated at shallow depths due to the strong stratification (Lincoln et al, 2016). Reanalysis of conductivity-temperature depth and acoustic Doppler current profiler finestructure data has not shown trends in turbulent mixing in recent decades either (Guthrie et al, 2013;Chanona et al, 2018).…”
Section: Ice Cover and Wind-driven Turbulencementioning
confidence: 99%